Application of Intelligent Data Analysis to Predict the Employment Success of Socially Vulnerable Groups - A. N. Kazinets (Цифровая трансформация)
In modern society, where social vulnerability is defined through the existence of population groups with limited material resources and a corresponding need for social support, complex challenges arise for researchers and practitioners in the field of socio-economic policy. The article discusses the use of data mining methods to predict the effectiveness of employment of socially vulnerable categories of the population. A multidimensional analysis of this issue was carried out, covering its various facets.